The Clinical Utility of miR-21 and let-7 in Non-small Cell Lung Cancer (NSCLC). A Systematic Review and Meta-Analysis - Pop-Bica, Cecilia; Pintea, Sebastian; Magdo, Lorand; Cojocneanu, Roxana; Gulei, Diana; Ferracin, Manuela; Berindan-Neagoe, Ioana (Frontiers in Oncology, 2020)
Non-small cell lung cancer (NSCLC) remains a problem worldwide due to its rapid progression and low rate of response to treatment. The heterogeneity of these tumors observed in histopathology exam but also in the mutational status and gene expression pattern makes this malignancy difficult to treat in clinic. The present study investigated the effect of miR-21 and let-7 family members as prognostic biomarkers in NSCLC patients based on the results published in different studies regarding this subject until March 2019. The analysis revealed that these two transcripts are steady biomarkers for prediction of patient outcome or survival. Upregulated expression of miR-21 is associated with poor outcome of patients with NSCLC [HR = 1.87, 95% CI = (1.41, 2.47), p < 0.001]. The analysis regarding let-7 family, specifically let-7a/b/e/f, revealed that downregulated expression of these transcripts predicts poor outcome for NSCLC patients [HR = 2.61, 95% CI = (1.58, 4.30), p < 0.001]. Besides, the reliability of these microRNAs is reflected in the fact that their prognostic significance is constant given the different sample types (tissue, FFPE tissue, serum, serum/plasma or exosomes) used in the selected studies.